Entrapment Neuropathies of the Shoulder - Alaia, Erin F.; Day, Michael S.; Alaia, Michael J. (Seminars in Musculoskeletal Radiology, 2022)
Entrapment neuropathies of the shoulder most commonly involve the suprascapular or axillary nerves, and they primarily affect the younger, athletic patient population. The extremes of shoulder mobility required for competitive overhead athletes, particularly in the position of abduction and external rotation, place this cohort at particular risk. Anatomically, the suprascapular nerve is most prone to entrapment at the level of the suprascapular or spinoglenoid notch; the axillary nerve is most prone to entrapment as it traverses the confines of the quadrilateral space.Radiographs should be ordered as a primary imaging study to evaluate for obvious pathology occurring along the course of the nerves or for pathology predisposing the patient to nerve injury. Magnetic resonance imaging plays a role in not only identifying any mass-compressing lesion along the course of the nerve, but also in identifying muscle signal changes typical for denervation and/or fatty atrophy in the distribution of the involved nerve.
Keywords: nerve; shoulder; magnetic resonance imaging